Enhanced expression of recombinant miraculin, a tasting modifying protein, in Nicotiana tabacum hairy roots using 18.2 heat shock protein promoter and terminator - Hong, La Viet; Giang, Nguyen Thu; Duc, Le Hoang; Ngoc, Pham Bich; Ha, Chu Hoang (Vietnam Journal of Biotechnology, 2021)
Miraculin, a taste modifier, is a protein that was first isolated from miracle fruit (Richadella dulcifica). It can change a sour taste into a sweet taste when sour acids are consumed, although it does not elicit a sweet response. Miraculin may have the potential in industry as a substitute for sugars and as artificial sweeteners. Since the miracle plant has low fruit productivity, mass production of miraculin is limited. Transgenic hairy root culture is a potential alternative system for the mass production of miraculin. In this study, we investigated the expression of recombinant miraculin in tobacco (Nicotiana tabacum) hairy roots. To increase miraculin expression, the heat shock protein 18.2 promoter and terminator were used to drive the expression of miraculin gene in a potential host system. Synthetic miraculin gene was transformed into Nicotiana tobacum leaf explants via Agrobacterium rhizogenes. The transgenic hairy root clones that contained synthetic miraculin gene showed rapid growth and reached maximum growth after 35-day culture. When the expression of miraculin gene was regulated by heat shock protein 18.2 promoter and heat shock protein terminator, the expression of recombinant miraculin increased than the control regulated by CaMV 35S promoter and nopaline synthase terminator. The recombinant miraculin was 19.97 ng per µg of the total soluble protein and equivalently with approximately 2% of the total soluble protein. For the first time, a taste modifying miraculin was successfully expressed in tobacco hairy root. The results in this study have given a promising approach for the application of the transgenic hairy root system to produce recombinant miraculin.